Design and calibration of a simple rainfall simulator - Dutta, Sunil Ch.; Apichart Anukularmphai; Banks, Robert B.; Eggers, Helmut; The Belgian Government (BangkoK : Asian Institute of Technology, 1979)
A simple rainfall simulator at a height of 2.5 meters above the ground surface and consisted of a steel frame, a net and spray nozzles used for determining different characteristics of rainfall such as, fall velocities of raindrops, drop size distribution, kinetic energy, momentum, at nine different rainfall intensities, varying from 21.34 mm/hr to 105.16 mm/hr and finally this simulator was calibrated to develop relationships among gate-valve pressure, rainfall intensities, drop diameters, rainfall distribution, drop size distribution. The average distribution efficiency of rainfall was found to be about 85%, which indicated that the rainfall distribution over the area covered by rain was quite uniform. In case of drop size distribution of rainfall, it was found that the drop size distribution curves followed a definite pattern. The median volume drop diameter of rainfall was found to be varied from 2.35 mm to 2.83 mm. As the height of fall for the simulated raindrops was only 2.5 meters, so the fall velocities attained by the drops were only 75% of the terminal velocities and due to this, the momentum of raindrop was also 75% of that of natural raindrop and kinetic energy of simulated rainfall was about 53% of that of natural rainfall.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1979
Keywords: Rain and rainfall